Oolalamaths : An innovative educational mathematics card game for kids / Siti Rosiah Mohamed ... [et al.] - Mohamed, Siti Rosiah; Mohd Din, Norlaila; Mohd Rosli, Nor Habibah; Bujang, Roziana; Mohd, Ainun Hafizah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Interactive learning in multiplication games is crucial among primary and secondary students to attract their interest in the learning process. Some of the students are weak in multiplication, which results in less interest in Mathematics subjects. The factors that contributed to this issue are the widely used of calculator device, the difficulty for students to memorize the basic multiplication numbers, the problem faced by the students to understanding the process or operation of calculation involved and also the traditional methods of teaching are less impressive. The objectives of the papers are to develop the enthusiasm of learning Mathematics using card games, to help students improve their focus and memory skills in multiplication subject and to share the card games ideas for learners and educators. The proposed gamed refers to Oolalamaths which was designed as an innovative perspective of learning while playing and memorizing. This game used as a teaching aid that was designed to help students acquire multiplication skill in a fun and easy way. The concept of this game is interactive learning, fun, and can be played in group. Oolalamaths consists of four Flashmaths Oolala multiplication table cards, 15 purple cards of the miracle of eleven, 20 green cards, 40 red cards and 12 green shape (geometry) cards that consist of figures that used to score in the games. The content of Oolalamaths helps students to master basic multiplication and other mathematical concepts. It is hoped that the design of the Oolalamaths educational game is useful and easily adopted not only for kids but also adults.